KOMITMEN TERHADAP ORGANISASI DILIHAT DARI KEADILAN KOMPENSASI STUDI KASUS DI SALAH SATU RUMAH SAKIT SWASTA DI KOTA SEMARANG - Ariyani Indriastuti; TH Susetyarsi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The Purpose of the research is to determine the effect of fairness compensation on organizational commitment. Fairness of compensation is indicated by salary, incentives, bonuses, benefits, insurance and pension guarantees. This research is a causal associative research using a quantitative approach. The sample of this study was nurses in one hospital at Semarang City. Data collection using questionnaires and interviews, the sampling technique is purposive sampling obtained 81 samples. Data analysis using multiple linear regression. The research indicate that: 1) Salary has no significant effect on organizational commitment, 2). Incentives have a positive and significant effect on organizational commitment. 3). bonuses have a positive and significant impact on organizational commitment. 4). Allowances have a positive and significant effect on organizational commitment. 5). Insurance has no significant effect on organizational commitment. 6). Pension insurance has a positive and significant effect on organizational commitment.